(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Monoammonium glycyrrhizinate (MASGA) is a water-soluble amphiphilic saponin that forms stable supramolecular complexes with poorly soluble drug substances, whereas the parameters of their preparation and standardization have thus far been described only in a fragmentary manner [1–3,8,9,11–13]. This study systematizes existing data on the structure and self-assembly of glycyrrhizinates, substantiates the role of MASGA as a matrix-forming excipient and a “mild solubilizer,” and demonstrates that complex formation with low-molecular-weight substrates (urea, thiourea, amino acids, cholesterol, and several pharmaceutical compounds) results in a multiple increase in aqueous solubility, accelerated dissolution, and enhanced bioavailability and biological activity [3,11–13,17–21,25,26,28]. A unified approach is proposed for the preparation of solid and semi-solid dosage forms based on MASGA, including mechanochemical co-milling, the solvent–evaporation method, lyophilization,and in situ self-assembly. Key criteria for their standardization are formulated: quantitative analysis of the components, control of stoichiometry and solid-state form, spectral “fingerprint,” dissolution profile, and in vitro and in vivo activity indicators. Taken together, these elements form the foundation for QbD-oriented design and validation of MASGA complexes as a standardized excipient for the delivery of poorly soluble drugs. The numerical parameter ranges provided in Sections 3.3–3.3.6 represent preliminary estimates (design assumptions) based on literature data and are subject to refinement in targeted experimental studies.